Evaluation Of The Architecture Of The Information System Of Seblak Sibocah Kencur Sales In Malang City Based On The Zachman Framework - Dorris Kurnia Tawana; Bhisma Pamungkas (International Journal of Information Systems and Technology, 2025)
In the digital era, information system integration and structure are crucial needs for MSMES in increasing efficiency and competitiveness. Seblak SiBocah Kencur, a culinary business in Malang City, has utilized a simple sales information system but does not yet have a documented and standardized system architecture. This study aims to evaluate the sales information system architecture using the Zachman Framework approach to map the system as a whole based on six perspectives and six main focuses. The method used is Applied Research with Research and System Development (RSD) through interviews, observations, and system documentation. The results of the study show weaknesses in the documentation of business strategies and data integration, even though networks and applications are already available. The resulting recommendations are in the form of a redesign of the information system architecture that supports managerial decision making and operational efficiency. This study provides a practical contribution in the form of an initial blueprint of the information system architecture that can be developed as a basis for digitalizing business processes as a whole in culinary MSMES .